Adverse Perinatal Outcomes Predicted by Prenatal Maternal Stress Among U.S. Women at the COVID-19 Pandemic Onset. Issue 3 (16th March 2021) - Preis, Heidi; Mahaffey, Brittain; Pati, Susmita; Heiselman, Cassandra; Lobel, Marci
Abstract: Background: High stress prenatally contributes to poor maternal and infant well-being. The coronavirus disease 2019 (COVID-19) pandemic has created substantial stress for pregnant women. Purpose: To understand whether stress experienced by women pregnant at the beginning of the pandemic was associated with a greater prevalence of adverse perinatal outcomes. Methods: Pregnant women across the USA aged ≥18 years old enrolled in a prospective cohort study during the pandemic onset (T1) in April–May 2020. This report focuses on the 1, 367 participants who gave birth prior to July–August 2020 (T2). Hierarchical logistic regression models predicted preterm birth, small for gestational age infants, and unplanned operative delivery from T1 stress, sociodemographic, and medical factors. Results: After controlling for sociodemographic and medical factors, preterm birth was predicted by high prenatal maternal stress, delivering an infant small for gestational age was predicted by interpersonal violence and by stress related to being unprepared for birth due to the pandemic, and unplanned cesarean or operative vaginal delivery was predicted by prenatal appointment alterations, experiencing a major stressful life event, and by stress related to being unprepared for birth due to the pandemic. Independent of these associations, African American women were more likely than other groups to deliver preterm. Conclusion: Pregnant women who are experiencing high stress during the COVID-19 pandemic are at risk of poorer perinatal outcomes. A longitudinal investigation is critical to determine whether prenatal maternal stress and resulting outcomes have longer-term consequences for the health and well-being of children born in the midst of the current pandemic. Abstract : Pregnant women who experienced greater stress during the COVID-19 pandemic onset were more likely to have a preterm birth, to deliver a small-for-gestational-age infant, and to have an unplanned operative delivery.